Addictive Behavior of Online Slot Game Players Psychoanalytic Perspective - Hanna Mazlin; Irma Nirmala Silki; Khaerudin Imawan; Aghnia Dian Lestari (Asian Journal of Social and Humanities, 2024)
One of the deviant acts that often occur and disturb the community is gambling. The act of gambling arises because of unstable conditions both in terms of religion, economy and morals. This study aims to determine the form or form of personality of online slot game players, especially among the community. In this study, the authors used a research method conducted with a qualitative. Based on the results of interviews with informants who play online slot games, it shows that they started playing online slot games through the scope of friendship or association. As a result, online slot games have become popular among the surrounding community. Even the players themselves realize that what they are doing is wrong and deviates from the norms of society. By using Freud's Psychoanalysis theory, there are 3 elements that influence human personality, namely Id, Ego and Superego. The element that has the most influence on the personality of online slot game players is Id. It can be concluded that the internet has an important role in the development of online gambling which affects individual personalities as well as the lives of society as a whole.